2021
DOI: 10.1111/hiv.13175
|View full text |Cite
|
Sign up to set email alerts
|

Participation, retention and uptake in a multicentre pre‐exposure prophylaxis cohort using online, smartphone‐compatible data collection

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…The higher level of retention observed in our center compared with previous studies did not appear to be explained by differences in participants’ characteristics. As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The higher level of retention observed in our center compared with previous studies did not appear to be explained by differences in participants’ characteristics. As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
“…As in other studies, patients were generally younger than 40 (between 62% and 81% in comparison with 71% in our patients) and were almost all MSM with only male sexual partners [ 2 , 4 , 5 , 6 , 11 , 19 , 20 , 21 , 22 , 26 , 27 ]. Characteristics regarding country of birth and work status were also similar in the studies for which this information was available [ 22 , 26 , 27 ]. Patients in our study showed a high (67%) but not unusual level of STI history; rates reported elsewhere ranged from 31% to 76% [ 2 , 17 , 22 , 24 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations